An investigation of bacteriocin nisin anti-cancer effects and FZD7 protein interactions in liver cancer cells. (1st October 2022) - Balcik-Ercin, Pelin; Sever, Belgin
Abstract: The bacteriocin, nisin, produced by Lactococcus and Streptococcus species during fermentation, is widely used for bio preservatives in a wide variety of foods. Liver cancer has a high mortality rate and is the fourth leading cause of cancer-related deaths worldwide. Recently, researchers have shown the anti-cancer effects of nisin through in vitro and in vivo studies. This study aimed to investigate the effect of nisin on liver cancer cell lines, which represented two subgroups of the disease model. Nisin exhibited significant growth inhibition and apoptosis in both cell lines, HuH-7, and SNU182. Drug resistance is the main problem in liver cancer and the epithelial-to-mesenchymal transition has a role in the development of drug resistance in hepatocellular carcinoma. The expression of EMT transcription factors ZEB1, SNAI1, and TWIST1 were analyzed depending on nisin treatment, TWIST1 expression was down-regulated after nisin treatment compared to the untreated SNU182 and HuH-7 cell lines. Besides, due to the reported correlation between the overexpression of Frizzled (FZD) proteins, specifically FZD7, in primary hepatocellular carcinomas (HCCs), molecular docking was assessed for Nisin A in the binding site of FZD7. Results confirmed that Nisin A was able to form important hydrogen bonding with key residues. This research not only determined the role of nisin in different liver cancer cell models but it also provided the first result of FZD7 and nisin interaction. Highlights: The nisin cytotoxic effect was evaluated. Nisin treatment caused cell cycle arrest. Nisin treatment changed the EMT transcription factors expression. Nisin binding with FZD7 involved H-bonding.